Spiritual Role Models in Fethullah GÃ¼lenâs Educational Philosophy - Yucel, Salih (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: Contemporary Turkish Islamic scholar, Fethullah Gülen, states that the world is in need of Islam and Islam is in need of representation or âtamsilâ. He believes that peopleâs ears are full but their eyes are hungry for role models in all areas of life, including educational institutions. In his philosophy, representation comes before communication or âtablighâ. When referring to âtamsilâ, Fethullah Gülen uses the term âHasani ruhâ or the spirit of Hasan, grandson of Prophet Muhammad SAW (peace be upon him). Hasan (radiallahu anh) symbolizes a loved leader who sacrifices for the peace, security, and good of people while striving to prevent conflict and bloodshed in the Muslim world. In Fethullah GÃ¼lenâs works, âHasani ruhâ refers to being altruistic, trustworthy, peaceful, and devoted to the service of humanity. I will examine the concept of âHasani ruhâ and explore the altruism of teachers as seen in the time they devote and financial support they give to the educational institutions established by Fethullah GÃ¼lenâs followers in the state of Victoria in Australia.KEY WORDS: Fethullah GÃ¼lenâs works, representation, âHasani ruhâ, altruism of teachers, and Gülen-inspired school in Victoria.===About the Author: Dr. Salih Yucel is a Lecturer at the School of Philosophical, Historical, and International Studies, Centre for Studies in Religion and Theology MU (Monash University), Clayton Campus, Victoria, Australia 3800. The author can be reached at: salih.yucel@monash.eduHow to cite this article? Yucel, Salih. (2011). âSpiritual Role Models in Fethullah GÃ¼lenâs Educational Philosophyâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.65-76. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 11, 2011); Revised (September 17, 2011); and Published (October 28, 2011).